Fungsi Strategis Bahasa Dalam Kegiatan Ekonomi: Sebuah Kajian Linguistik Lanskap Iklan Restoran Di Kota Pontianak - Dwi Purwanto; Filia Filia (LITERATUS, 2020)
The ease of access to information, communication and transportation provides a golden opportunity for the development of the Indonesian language. As a member of the MEA and G20, as well as the country with the fourth largest population in the world, Indonesian has the potential to be seen by the world economically as a very strategic language. However, the development of information and communication technology, as well as the ease of mobility, have made it easier for Indonesians to get exposed to foreign languages. This has resulted in many language activists worried that Indonesian will be eroded by foreign languages ??such as English. Due to the problem, this study was conducted to identify the extent to which the application of Indonesian in accordance with KBBI, PUPI and PUEBI was implemented, particularly in the daily economic activities of local residents. This study was conducted using linguistic landscape techniques and was carried out in the Southeast Pontianak sub-district, Pontianak City, West Kalimantan. The study successfully identified as many as 1465 Indonesian terms, 110 foreign language terms, and 95 regional language terms. Based on this study, it can be concluded that in economic activities, especially those related to basic needs, Pontianak city residents still have sufficient knowledge and awareness to use Indonesian, both outdoors and in public spaces. In addition, the study carried out also shows at least five roles for foreign languages ??and regional languages ??that cannot be replaced by an Indonesian equivalent.